Polyolefin Adhesive Film

The polyolefin adhesive film with a polypropylene support layer and maleic anhydride-modified adhesive layer addresses VOC volatilization and adhesive strength issues, providing durable bonding with aluminum foil in harsh conditions.

JP7617966B2Active Publication Date: 2025-01-20NANYA PLASTICS CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023032540
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-12-13
Filing Date
2023-03-03
Publication Date
2025-01-20
Estimated Expiration
2043-03-03

AI Technical Summary

Technical Problem

Conventional aluminum plastic film packaging materials face issues with volatile organic solvents (VOC) volatilization and reduced adhesive strength due to high temperature and humidity, leading to insufficient bonding between polyolefin film and aluminum foil.

Method used

A polyolefin adhesive film with a support layer made of polypropylene film and an adhesive layer formed by coextrusion using a first polyolefin copolymer modified with maleic anhydride, which is formed by copolymerizing C2 to C4 olefin molecules, with specific grafting ratios and melt indices, allowing direct thermal lamination onto metal aluminum foil without additional adhesives.

Benefits of technology

The polyolefin adhesive film achieves self-bonding properties, preventing VOC volatilization and maintaining adhesive strength in high temperature and humid environments, ensuring effective bonding with aluminum foil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617966000001
    Figure 0007617966000001
  • Figure 0007617966000002
    Figure 0007617966000002
  • Figure 0007617966000003
    Figure 0007617966000003
Patent Text Reader

Abstract

To provide a polyolefin adhesive film that includes a support layer and an adhesive layer formed on a side surface of the support layer by co-extrusion.SOLUTION: The support layer is a polypropylene film. The adhesive layer is formed of a first polyolefin copolymer modified with maleic anhydride. The first polyolefin copolymer is formed by copolymerization of at least two kinds of C2 to C4 olefin molecules. A first graft ratio of the maleic anhydride grafted onto the first polyolefin copolymer is between 0.5% and 5%, and a first melt index of the first polyolefin copolymer is between 3 g / 10 min and 5 g / 10 min.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to adhesive films, and more particularly to polyolefin adhesive films. [Background technology]

[0002] As shown in Figure 5, conventional aluminum plastic film packaging materials often adopt a dry composite polyolefin film PL / aluminum foil AF. The two materials are bonded together with an adhesive layer GL (e.g., polyester adhesive or polyurethane adhesive). However, conventional aluminum plastic film packaging materials have a problem in that volatile organic solvents (VOCs) easily evaporate during lamination. In addition, when conventional aluminum plastic film packaging materials are left in a high-temperature and high-humidity environment for a long time, the adhesive strength between the polyolefin film PL and the aluminum foil AF deteriorates, leading to a problem of insufficient adhesive strength.

[0003] Therefore, in view of the fact that the above-mentioned problems can be improved, the inventors conducted intensive research and applied scientific theory, and as a result, arrived at the present invention as a method that is rational in design and can effectively improve the above-mentioned problems. Summary of the Invention [Problem to be solved by the invention]

[0004] The technical problem that the present invention seeks to solve is to provide a polyolefin adhesive film that addresses the shortcomings of the prior art. [Means for solving the problem]

[0005] In order to solve the above technical problems, one technical means adopted by the present invention provides a polyolefin adhesive film comprising a support layer which is a polypropylene film and an adhesive layer formed on one side of the support layer by coextrusion. The adhesive layer is a first polyolefin copolymer modified with maleic anhydride. The first polyolefin copolymer is formed by copolymerizing at least two of C2-C4 olefin molecules. The first graft ratio of the maleic anhydride in the first polyolefin copolymer is 0.5%-5%, and the first melt index of the first polyolefin copolymer is 3g / 10min-5g / 10min.

[0006] Preferably, in the adhesive layer, the first melt index of the first polyolefin copolymer is 3 g / 10 min to 4 g / 10 min.

[0007] Preferably, the support layer is a cast polypropylene film and the support layer comprises a propylene block polymer, a vinyl elastomer, and a second polyolefin copolymer.

[0008] Preferably, in the support layer, the propylene block polymer includes a block composed of an ethylene propylene elastic rubber, the weight percentage of the ethylene propylene elastic rubber in the propylene block polymer is 18% or more, the vinyl-based elastomer is an ethylene / butene elastomer, and the weight percentage of ethylene in the vinyl-based elastomer is 30% or more.

[0009] Preferably, the second polyolefin copolymer in the support layer is modified with maleic anhydride and formed by copolymerizing at least two of C2 to C4 olefin molecules, a second graft ratio of the maleic anhydride in the second polyolefin copolymer is 0.5% to 5%, and a second melt index of the second polyolefin copolymer is 3 g / 10 min to 5 g / 10 min.

[0010] Preferably, in the support layer, the content of the propylene block polymer is 50 wt% to 90 wt%, the content of the vinyl elastomer is 5 wt% to 30 wt%, and the content of the second polyolefin copolymer modified with maleic anhydride is 5 wt% to 20 wt%, with the total weight of the support layer being 100 wt%.

[0011] Preferably, the polyolefin adhesive film further comprises a heat seal layer formed on the other side of the support layer by coextrusion.

[0012] Preferably, the heat seal layer is a propylene polymer, the propylene polymer being at least one of a propylene copolymer and a propylene homopolymer.

[0013] Preferably, the heat seal strength of the heat seal layer of the polyolefin adhesive film is greater than or equal to 80 N / 15 mm, measured according to standard measurement QB / T2358-1998.

[0014] Preferably, the adhesive layer has a first thickness of 4 μm to 12 μm, the support layer has a second thickness of 15 μm to 35 μm, and the heat seal layer has a third thickness of 4 μm to 12 μm.

[0015] Preferably, the polyolefin adhesive film is bonded to the metal aluminum foil via an adhesive layer, and the peel strength between the polyolefin adhesive film and the metal aluminum foil is 10 N / 15 mm or more.

[0016] Preferably, in a physical property measurement of a lithium battery / peel measurement after immersion in an electrolyte, the aluminum-plastic laminate film obtained by laminating the polyolefin adhesive film and the metal aluminum foil has another peel strength of more than 8.5 N / 15 mm after immersion for 168 hours in an electrolyte environment at 85°C. Effect of the Invention

[0017] As an advantageous effect of the present invention, the polyolefin adhesive film of the present invention has the following technical features: "a support layer which is a polypropylene film", "an adhesive layer formed on one side of the support layer by coextrusion", and "the adhesive layer is a first polyolefin copolymer modified with maleic anhydride. The first polyolefin copolymer is formed by copolymerizing at least two types of C2-C4 olefin molecules. The first graft ratio of the maleic anhydride in the first polyolefin copolymer is 0.5%-5%, and the first melt index of the first polyolefin copolymer is 3g / 10min-5g / 10min". Therefore, the adhesive layer formed on the support layer by coextrusion can be directly thermally laminated to the metal aluminum foil, eliminating the need to use another polyester adhesive or polyurethane adhesive to bond it.

[0018] The polyolefin adhesive film according to the present invention has self-adhesiveness and can solve the problem of volatile organic solvent (VOC) volatilization in the conventional technology. In addition, the polyolefin adhesive film 100 according to the embodiment of the present invention can solve the problem of strength reduction caused by a high temperature and humidity environment for a long time in the conventional dry composite polyolefin film / aluminum foil packaging material. [Brief description of the drawings]

[0019] [Figure 1] 1 is a schematic diagram of a polyolefin adhesive film according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram (1) of laminating the polyolefin adhesive film of FIG. 1 to an aluminum foil. [Diagram 3] FIG. 2 is a schematic diagram (II) of bonding the polyolefin adhesive film of FIG. 1 to aluminum foil. [Figure 4] FIG. 2 is a schematic diagram of a polyolefin adhesive film according to a second embodiment of the present invention. [Diagram 5]FIG. 1 is a schematic diagram of an aluminum plastic film packaging material according to the prior art. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] In order to better understand the features and technical contents of the present invention, please refer to the following detailed description of the present invention and the accompanying drawings, which are provided for reference and explanation only and are not intended to limit the scope of the present invention.

[0021] Hereinafter, the embodiments of the present invention will be described by certain specific embodiments, and those skilled in the art can understand the advantages and effects of the present invention based on the contents disclosed in this specification. The present invention can be implemented or applied by other different specific embodiments, and each detail in this specification can be modified and changed based on different perspectives and applications without departing from the concept of the present invention. The technical contents according to the present invention will be described in more detail based on the following embodiments, but the disclosed contents do not limit the scope of protection of the present invention. It should be understood that, although various elements or signals may be described in this specification using terms such as "first", "second", and "third", these elements or signals are not limited by these terms. These terms are mainly used to distinguish one element from another element, or one signal from another signal. In addition, the term "or" used in this specification may include any one or more combinations of the relevant items listed according to the actual situation.

[0022] [First embodiment] As shown in Figures 1 to 3, in the first embodiment of the present invention, a polyolefin adhesive film 100 includes an adhesive layer 1, a support layer 2, and a heat seal layer 3. The adhesive layer 1 is formed on one side of the support layer 2 (for example, the upper surface of the support layer 2 in Figure 1). The heat seal layer 3 is formed on the other side of the support layer 2 (for example, the lower surface of the support layer 2 in Figure 1). That is, the support layer 2 is between the adhesive layer 1 and the heat seal layer 3.

[0023] In this embodiment, the adhesive layer 1, the support layer 2 and the heat seal layer 3 of the polyolefin adhesive film 100 are formed as a laminate structure by co-extrusion, i.e., the adhesive layer 1 is formed on the support layer 2 by co-extrusion.

[0024] As shown in Figures 2 and 3, the polyolefin adhesive film 100 is combined with a metal aluminum foil AF (aluminum foil) via the adhesive layer 1. The support layer 2 provides impact resistance and support to the polyolefin adhesive film 100. The heat seal layer 3 provides heat sealability to the polyolefin adhesive film 100. Thus, the polyolefin adhesive film 100 is applied to packaging materials, particularly packaging materials for lithium batteries or packaging materials for electronic products, but the present invention is not limited thereto.

[0025] Regarding the thickness, the first thickness T1 of the adhesive layer 1 is 4 μm to 12 μm, and preferably 6 μm to 10 μm. The second thickness T2 of the support layer 2 is 15 μm to 35 μm, and preferably 20 μm to 28 μm. The third thickness T3 of the heat seal layer 3 is 4 μm to 12 μm, and preferably 6 μm to 10 μm.

[0026] More specifically, the adhesive layer 1 is formed of a first polyolefin copolymer modified with maleic anhydride (MAH).

[0027] The first polyolefin copolymer is formed, for example, by copolymerizing at least two of C2 to C4 olefin molecules. Those skilled in the art are familiar with the fact that the C2 olefin molecule is ethylene (PE), the C3 olefin molecule is propylene (PP), and the C4 olefin molecule is butene, such as 1-butene.

[0028] For example, the raw materials constituting the first polyolefin copolymer may be, for example, C2 olefin molecules and C3 olefin molecules, C2 olefin molecules and C4 olefin molecules, C3 olefin molecules and C4 olefin molecules, or C2-C4 olefin molecules. Preferably, the raw materials constituting the first polyolefin copolymer may be C3 olefin molecules and C4 olefin molecules, but the present invention is not limited thereto. In addition, the weight ratio of two kinds of olefin molecules (for example, C3 and C4, or C2 and C4) may be, for example, 30:70 to 70:30 (preferably 40:60 to 60:40), but the present invention is not limited thereto.

[0029] It is noteworthy that the first polyolefin copolymer according to this embodiment is formed by copolymerizing at least two types of C2 to C4 olefin molecules, and therefore the adhesive layer 1 has both higher transparency and adhesive strength.

[0030] More specifically, in this embodiment, the first polyolefin copolymer is modified with maleic anhydride (MAH). The first polyolefin copolymer modified with maleic anhydride has a carboxyl group (-COOH), so that the polarity of the first polyolefin copolymer is significantly improved. As a result, the first polyolefin copolymer modified with maleic anhydride has better water solubility and adhesive strength than an unmodified polyolefin copolymer, and is more suitable for use as an adhesive layer.

[0031] The maleic anhydride may be, for example, grafted onto a first polyolefin copolymer. More specifically, the maleic anhydride may be, for example, melt-grafted onto a polyolefin copolymer. The melt-grafting may be, for example, performed in a single screw extruder, a twin screw extruder, or a rheometer. Preferably, the melt-grafting is performed in a twin screw extruder.

[0032] The adhesive layerIn the composition according to claim 1, the content of the first polyolefin copolymer is 90 wt% or more, and preferably 95 wt% or more. Also, the first graft ratio of the maleic anhydride in the first polyolefin copolymer is preferably 0.5% to 5%.

[0033] It is noteworthy that in this embodiment, when the first graft ratio of maleic anhydride is controlled to 0.5% to 5%, excellent adhesive strength can be obtained. When the first graft ratio of maleic anhydride is less than 0.5%, the adhesive strength of the adhesive layer 1 deteriorates. On the other hand, when the first graft ratio of maleic anhydride is more than 5%, the adhesive layer 1 becomes too hard after being bonded to the aluminum foil, affecting the flex resistance of the packaging material.

[0034] It should be noted that the grafting rate of maleic anhydride in this specification can be analyzed, for example, by a Fourier transform infrared spectrometer (FTIR). The Fourier transform infrared spectrometer can perform a qualitative analysis of whether maleic anhydride is grafted to the molecular chain of the polyolefin copolymer, and can also quantitatively determine the grafting rate of maleic anhydride. According to the infrared absorption spectrum, maleic anhydride grafting can be performed at 1725 cm -1 , 1790cm -1 The maleic anhydride has a notable absorption peak at 1000 nm, which is a characteristic peak of the carboxyl group in the maleic anhydride. The quantitative analysis of the graft ratio of the maleic anhydride can be performed based on, for example, the Beer-Lambert law.

[0035] More specifically, in this embodiment, the first melt index (melt flow index, MI) of the modified first polyolefin copolymer is 3 g / 10 min to 5 g / 10 min, and preferably 3 g / 10 min to 4 g / 10 min.

[0036] It is noteworthy that in this embodiment, when the first melt index of the first polyolefin copolymer is controlled to 3 g / 10 min to 5 g / 10 min, it provides the adhesive layer 1 with better adhesion and transparency, as well as better appearance (e.g., smooth surface, no noticeable streaks) and better touch. If the first melt index of the first polyolefin copolymer exceeds the above range, it may cause problems such as poor adhesion of the adhesive layer 1 and streaks on the surface of the packaging material.

[0037] It should be noted that the melt index in this specification is the weight of the polyolefin copolymer extruded in 10 minutes. Its unit is g / 10 min. The melt index indicates the fluidity of the resin in a molten state, and the larger the melt index, the smaller the molecular weight and the better the fluidity. Conversely, the smaller the melt index, the larger the molecular weight and the worse the fluidity. In this embodiment, the melt index is measured at 190°C and a load of 2.16 kg based on ASTM D1238.

[0038] It is worth noting that the first polyolefin copolymer is produced, for example, by processing and granulating the copolymer in a twin-screw extruder in the presence of peroxide (0.3 to 0.6%), and maleic anhydride is melt-grafted. In the extrusion process, the melt index of the first polyolefin copolymer can also be controlled.

[0039] More specifically, the first polyolefin copolymer formed by granulation forms the adhesive layer 1 which is applied to one surface of the support layer 2, for example by co-extrusion.

[0040] According to the above technical solution, the polyolefin adhesive film 100 according to the embodiment of the present invention is thermally laminated with the metal aluminum foil AF via its own adhesive layer 1, as shown in Figures 2 and 3, without the need for bonding with other polyester adhesives or polyurethane adhesives.

[0041] The polyolefin adhesive film 100 according to the present invention not only has self-adhesiveness, but also solves the problem of volatile organic solvent (VOC) volatilization in the conventional technology. In addition, the polyolefin adhesive film 100 according to the embodiment of the present invention solves the problem of strength reduction caused by a high temperature and humidity environment for a long time in the conventional technology of dry composite polyolefin film / aluminum foil packaging material.

[0042] As shown in FIG. 1, the support layer 2 is a cast polypropylene film (CPP film, also called unstretched polypropylene film) for providing the polyolefin adhesive film 100 with impact resistance and the support required for packaging materials.

[0043] More specifically, the support layer 2 contains a propylene block polymer, a vinyl elastomer, a second polyolefin copolymer modified with maleic anhydride (MAH modified polyolefin copolymer), and a lubricant.

[0044] The content of the propylene block polymer is 50 wt% to 90 wt%, and preferably 60 wt% to 80 wt%, based on the total weight of the support layer 2 being 100 wt%. The content of the vinyl elastomer is 5 wt% to 30 wt%, and preferably 15 wt% to 25 wt%, based on the total weight of the support layer 2 being 100 wt%. The content of the second polyolefin copolymer modified with maleic anhydride is 5 wt% to 20 wt%, and preferably 5 wt% to 15 wt%, based on the total weight of the support layer 2 being 100 wt%. The content of the lubricant is 100 ppm to 5,000 ppm, and preferably 1000 ppm to 4,000 ppm, based on the total weight of the support layer 2 being 100 wt%.

[0045] More specifically, the propylene block polymer includes a block composed of ethylene-propylene rubber (EPR), and the weight percentage of the ethylene-propylene rubber in the propylene block polymer is 18% or more, and preferably 18% to 30%, but the present invention is not limited thereto.

[0046] It is particularly noteworthy that the weight ratio of the ethylene propylene elastic rubber in the propylene block polymer satisfies the above weight percentage (for example, 18% to 30%), thereby providing the support layer 2 with good punchability.

[0047] More specifically, the vinyl elastomer is, for example, an ethylene / butene elastomer, which is a copolymer of ethylene, butene, and a small amount of bridging terminal monomers having carboxylic acid groups. The weight percentage of ethylene in the vinyl elastomer is 30% or more, and preferably 30% to 60%. Thus, the vinyl elastomer provides the support layer 2 with excellent punchability and prevents whitening that occurs during punching.

[0048] The second polyolefin copolymer modified with maleic anhydride in the support layer has, for example, similar material characteristics to those of the adhesive layer 1. The second polyolefin copolymer is formed by copolymerizing at least two of C2-C4 olefin molecules. More specifically, the second graft ratio of the maleic anhydride in the second polyolefin copolymer is 0.5%-5%. The second melt index of the second polyolefin copolymer modified with maleic anhydride is 3g / 10min-5g / 10min.

[0049] In this embodiment, the support layer 2 contains a second polyolefin copolymer (e.g., 5 to 20 wt%) modified with a small amount of maleic anhydride, and therefore the support layer 2 has a high affinity with the adhesive layer 1, thereby providing good interlayer adhesion strength between the support layer 2 and the adhesive layer 1.

[0050] If the content of the second polyolefin copolymer modified with maleic anhydride in the support layer 2 is lower than the above content range, the interlayer adhesive strength deteriorates, whereas if the content of the second polyolefin copolymer modified with maleic anhydride in the support layer 2 is higher than the above content range, the punching of the packaging material deteriorates.

[0051] To further explain, the lubricant may be, for example, silicon dioxide (SiO2) or talc, which can improve the punchability and processability of the support layer 2, but the present invention is not limited thereto.

[0052] To further explain, the visible light transmittance of the support layer 2 may be 80% to 99%, and the haze value may be 5% to 30%, but the present invention is not limited thereto. It should be noted that the visible light transmittance and the haze value are measured based on ASTM D1003.

[0053] Continuing with FIG. 1, the heat seal layer 3 is formed from a propylene polymer.

[0054] For example, the propylene polymer may be at least one of a propylene copolymer (co-PP) and a propylene homopolymer (homo-PP). The propylene copolymer may be formed, for example, by copolymerizing propylene and ethylene. In this embodiment, the weight ratio of ethylene in the propylene copolymer is preferably 2% or less. Thereby, the heat seal layer 3 can provide the polyolefin adhesive film 100 with better heat seal strength.

[0055] According to the above-mentioned technical solution, the polyolefin adhesive film 100 according to the embodiment of the present invention, as shown in FIG. 2 and FIG. 3, is formed on the support layer 2 by coextrusion, and is directly heat-laminated with the metal aluminum foil AF, without the need for bonding with other polyester adhesives or polyurethane adhesives. The polyolefin adhesive film 100 according to the present invention not only has self-adhesiveness, but also solves the problem of volatile organic solvents (VOCs) volatilizing in the conventional technology. In addition, the polyolefin adhesive film 100 according to the embodiment of the present invention can solve the problem of insufficient adhesive strength due to strength reduction caused by long-term high temperature and humidity environment of the dry composite polyolefin film / aluminum foil packaging material in the conventional technology. In addition, the heat seal layer 3 of the polyolefin adhesive film 100 according to the present invention has excellent heat seal strength. The heat seal strength of the polyolefin adhesive film 100 according to the embodiment of the present invention measured according to QB / T2358-1998 can reach 80N / 15mm or more. The measurement conditions are, for example, a temperature of 180°C, a pressure of 1 kgf / cm2, heat sealing for 3 seconds, and then the sample is cut to 15 mm x 15 mm and measured. The polyolefin adhesive film has a peel strength of more than 8.5 N / 15 mm even after immersion in an electrolyte environment at 85°C for 168 hours. The polyolefin adhesive film 100 according to the embodiment of the present invention is applied to packaging materials, in particular, packaging materials for lithium batteries or packaging materials for electronic products.

[0056] In order to demonstrate the above technical effects of the polyolefin adhesive film according to the present invention, the following will be described with Examples 1 to 4 and Comparative Examples 1 to 3. Among them, Examples 1 to 4 are a group that demonstrates the technical effects of the present invention, and Comparative Examples 1 to 3 are a group that has poor test effects. However, these examples are provided for the purpose of understanding the present invention, and the present invention is not limited thereto.

[0057] <Example 1> A polyolefin adhesive film having a three-layer laminate structure in which an adhesive layer, a support layer, and a heat seal layer were laminated in this order was formed by coextrusion. The adhesive layer was formed of a first polyolefin copolymer modified with maleic anhydride. The first polyolefin copolymer was formed by copolymerizing propylene (C3) and butene (C4). The content of the first polyolefin copolymer was 99.5 wt%, the graft ratio of maleic anhydride (MA) in the first polyolefin copolymer was 0.5%, and the melt index (MI) of the first polyolefin copolymer was 3.2 g / 10 min. The total weight of the support layer was 100 wt%, and the support layer contained 70 wt% of a propylene block polymer, 20 wt% of a vinyl-based elastomer (ethylene / butene elastomer), 10 wt% of a second polyolefin copolymer modified with maleic anhydride, and a trace amount of SiO2. The heat seal layer was composed of a propylene copolymer (co-PP) formed by copolymerizing propylene and ethylene, and the weight ratio of ethylene was 2% or less. The adhesive layer had a thickness of 8 μm, the support base layer had a thickness of 24 μm, and the heat seal layer had a thickness of 8 μm. The haze value of the polyolefin adhesive film of <Example 1> was 6%, and the adhesive film had no significant streaks in appearance. The heat seal strength of the polyolefin adhesive film measured according to QB / T2358-1998 was 81 N / 15 mm. The polyolefin adhesive film was bonded to an aluminum foil via the adhesive layer, and the peel strength between the polyolefin adhesive film and the aluminum foil was 10.2 N / 15 mm. In addition, the aluminum-plastic laminated film formed by laminating the polyolefin adhesive film and aluminum foil was immersed in an electrolyte environment at 85°C for 168 hours, and then measured, and the aluminum-plastic laminated film still had a peel strength (interlayer adhesive strength) of 8.5N / 15mm, indicating that the polyolefin adhesive film has excellent resistance to high temperature and high humidity environments. In addition, the aluminum-plastic laminated film could withstand bending 12 times and had a punching height of 6mm, and was used as a packaging material for lithium batteries.

[0058] <Example 2> The manufacturing conditions of <Example 2> were almost the same as those of <Example 1>. The differences between them are that in the adhesive layer of <Example 2>, the first polyolefin copolymer was formed by copolymerization of propylene (C3) and butene (C4), the content of the first polyolefin copolymer was 97 wt%, and the graft ratio of maleic anhydride (MA) in the first polyolefin copolymer was 3%. The melt index (MI) of the first polyolefin copolymer was 3.1 g / 10 min. The haze value of the polyolefin adhesive film of <Example 2> was 7%, and the adhesive film had no noticeable streaks in appearance. The heat seal strength of the polyolefin adhesive film measured according to QB / T2358-1998 was 82 N / 15 mm. The peel strength between the polyolefin adhesive film and the aluminum foil was 14.2 N / 15 mm. The aluminum-plastic laminated film formed by laminating the polyolefin adhesive film and aluminum foil was immersed in an electrolyte environment at 85°C for 168 hours, and then measured, and the aluminum-plastic laminated film still had a peel strength of 13.2N / 15mm. In addition, the aluminum-plastic laminated film could withstand 13 bending cycles and a punching height of 6.5mm, making it suitable for use as a packaging material for lithium batteries.

[0059] <Example 3> The manufacturing conditions of <Example 3> were almost the same as those of <Example 1>. The differences between them are that in the adhesive layer of <Example 3>, the first polyolefin copolymer was formed by copolymerization of propylene (C3) and butene (C4), the content of the first polyolefin copolymer was 95 wt%, and the graft ratio of maleic anhydride (MA) in the first polyolefin copolymer was 5%. The melt index (MI) of the first polyolefin copolymer was 3.4 g / 10 min. The haze value of the polyolefin adhesive film of <Example 3> was 6.5%, and the adhesive film had no noticeable streaks in appearance. The heat seal strength of the polyolefin adhesive film measured according to QB / T2358-1998 was 81 N / 15 mm. The peel strength between the polyolefin adhesive film and the aluminum foil was 13.2 N / 15 mm. The aluminum-plastic laminated film formed by laminating the polyolefin adhesive film and aluminum foil was immersed in an electrolyte environment at 85°C for 168 hours, and then measured, and the aluminum-plastic laminated film still had a peel strength of 12.0N / 15mm.In addition, the aluminum-plastic laminated film could withstand 11 bending cycles and had a punching height of 5mm, making it suitable for use as a packaging material for lithium batteries.

[0060] <Example 4> The manufacturing conditions were almost the same as those of <Example 1>. As for the differences, in the adhesive layer of <Example 4>, the first polyolefin copolymer was formed by copolymerization of ethylene (C2) and butene (C4), and the content was 97 wt%, and the graft ratio of maleic anhydride (MA) in the first polyolefin copolymer was 3%. The melt index (MI) of the first polyolefin copolymer was 3.2 g / 10 min. The haze value of the polyolefin adhesive film of <Example 4> was 15%, and the appearance of the adhesive film could not be observed. The heat seal strength of the polyolefin adhesive film measured according to QB / T2358-1998 was 83 N / 15 mm. The peel strength between the polyolefin adhesive film and the aluminum foil was 12.8 N / 15 mm. The aluminum-plastic laminated film formed by laminating the polyolefin adhesive film and aluminum foil was immersed in an electrolyte environment at 85°C for 168 hours, and then measured. The aluminum-plastic laminated film still had a peel strength of 11.2N / 15mm. The aluminum-plastic laminated film also had a bending resistance of 12 times and a punching height of 6mm. Although the haze value of the polyolefin adhesive film was high, it was still suitable as a packaging material for lithium batteries.

[0061] <Comparative Example 1> The manufacturing conditions were almost the same as those of the <Example 1>. As for the differences, in the adhesive layer of <Comparative Example 1>, the first polyolefin copolymer was formed by copolymerization of propylene (C3) and butene (C4), and the content was 94 wt%, and the graft ratio of maleic anhydride (MA) in the first polyolefin copolymer was 6%. The melt index (MI) of the first polyolefin copolymer was 3.5 g / 10 min. The haze value of the polyolefin adhesive film of <Comparative Example 1> was 7.5%, and the adhesive film had no noticeable streaks in appearance. The heat seal strength of the polyolefin adhesive film measured according to QB / T2358-1998 was 80.5 N / 15 mm. The peel strength between the polyolefin adhesive film and the aluminum foil was 13.5 N / 15 mm. The aluminum-plastic laminated film formed by laminating the polyolefin adhesive film and the aluminum foil was immersed in an electrolyte environment at 85°C for 168 hours, and then measured. The aluminum-plastic laminated film still had a peel strength of 13N / 15mm. In addition, the aluminum-plastic laminated film could only withstand 7 bending cycles, and the punching height was only 4.5mm. According to the results of the experiment, the bending cycles and punching height of the polyolefin adhesive film of Comparative Example 1 were both lower than those of Examples 1 to 4, and it was not applied as a packaging material for lithium batteries. The reason for the poor physical properties may be that the first graft ratio of the first polyolefin copolymer of maleic anhydride (MA) in Comparative Example 1 was too high (6%), exceeding the ideal value of 5%, so that the hardness of the polyolefin adhesive film and aluminum foil laminated together was too high to withstand bending and punching.

[0062] <Comparative Example 2> The manufacturing conditions were almost the same as those of the <Example 1>. As for the differences, in the adhesive layer of <Comparative Example 2>, the first polyolefin copolymer was entirely composed of propylene (C3) and butene (C4), the first polyolefin copolymer did not have maleic anhydride grafts, and the melt index (MI) of the first polyolefin copolymer was 5g / 10min. The haze value of the polyolefin adhesive film of <Comparative Example 2> was 6.2%, and the appearance had no significant streaks. The heat seal strength of the polyolefin adhesive film measured according to QB / T2358-1998 was 82N / 15mm. The peel strength between the polyolefin adhesive film and the aluminum foil was only 5.2N / 15mm. The aluminum-plastic laminate film formed by laminating the polyolefin adhesive film and the aluminum foil was immersed in an electrolyte environment at 85°C for 168 hours and then measured, and the aluminum-plastic laminate film had a peel strength of only 3.2N / 15mm. The aluminum plastic laminated film had a bending resistance of 10 times and a punching height of 6 mm. The polyolefin adhesive film of <Comparative Example 2> was not modified with maleic anhydride, and therefore had poor interlayer peel strength.

[0063] <Comparative Example 3> The manufacturing conditions were almost the same as those of the <Example 1>. As for the differences, in the adhesive layer of <Comparative Example 3>, the first polyolefin copolymer was formed of propylene (C3) and butene (C4), the content was 97 wt%, the graft ratio of maleic anhydride (MA) in the first polyolefin copolymer was 3%, and the melt index (MI) of the first polyolefin copolymer was 7 g / 10 min. The haze value of the polyolefin adhesive film of <Comparative Example 3> was 6.1%, and the adhesive film had noticeable streaks in its appearance. The heat seal strength of the polyolefin adhesive film measured according to QB / T2358-1998 was 83 N / 15 mm. The peel strength between the polyolefin adhesive film and the aluminum foil was 11.2 N / 15 mm. The aluminum-plastic laminated film formed by laminating the polyolefin adhesive film and aluminum foil was immersed in an electrolyte environment at 85°C for 168 hours, and then measurements were performed, showing that the aluminum-plastic laminated film had a peel strength of 9.5N / 15mm. The aluminum-plastic laminated film was able to withstand 11 bending cycles and a punching height of 6mm. A possible reason for this is that the polyolefin adhesive film of Comparative Example 3 had a too high melt index (MI of more than 5g / 10min) and had noticeable streaks on its appearance, making it unsuitable as a packaging material for lithium batteries.

[0064] It should be noted that the methods for measuring the "haze value" and "heat seal strength" have been explained in the preceding section on the preferred embodiment of the invention, and therefore will not be explained here in a redundant manner.

[0065] To explain further, the "peel strength" in this specification is the maximum force required to peel a unit width from the contact surface of materials bonded to each other (for example, the peel strength between a polyolefin adhesive film and an aluminum foil). A universal testing machine is used as a measuring device for measuring the peel strength. The measurement error of the test machine is within ±1% of the actual value. Regarding the measurement environment, the sample was left at a temperature of 23°C ±2°C and a relative humidity of 50% ±5% for more than 4 hours and then measured. Regarding the manufacture of the sample, the object to be measured was cut into five samples with a width of 15.0 mm ±0.1 mm and a length of 200 mm so as to be uniform by removing 50 mm from both ends in the width direction. The measurement method was such that both ends of the peeled part of the sample were clamped by the upper and lower jigs of the testing machine, respectively, and the vertical axis of the peeled part of the sample was appropriately fitted so as to overlap with the center line of the upper and lower jigs. The measurement speed was 300 mm / min ±30 mm / min, and the peel force curve of the peeling process of the sample was recorded. The average peel strengths of the samples in the longitudinal and transverse directions were measured and expressed as the measurement results (with two significant figures) in units of N / 15 mm.

[0066] To explain further, the "number of bending times" referred to in this specification is the number of times that the aluminum-plastic laminated film formed after laminating the polyolefin adhesive film to the aluminum foil can withstand being folded in four (the number of times without cracks occurring). Also, the "punching height" referred to in this specification is the height recorded when the aluminum-plastic laminated film is cold-pressed using a 5 cm x 6 cm die for a lithium battery, and the unit is mm.

[0067] The appearance of the packaging material was evaluated by a tester who observed the surface of the biaxially oriented polypropylene film of the packaging material with the naked eye (observation distance was about 30 cm). If no significant streaks were observed, it was rated as "no streaks." If significant streaks were observed, it was rated as "significant streaks." If the haze value of the packaging material was too high, it was rated as "not observable."

[0068] [Second embodiment] As shown in Figure 4, the second embodiment of the present invention provides a polyolefin adhesive film 100' comprising an adhesive layer 1 and a support layer 2. Wherein, the adhesive layer 1 is formed on the support layer 2 by co-extrusion. Different from the above first embodiment, the polyolefin adhesive film 100' of the second embodiment of the present invention may not include a heat seal layer 3, for example.

[0069] In the second embodiment, the material characteristics of the adhesive layer 1 and the support layer 2 are similar to those of the first embodiment, so they will not be described here repeatedly.

[0070] Due to the above-mentioned configuration, the polyolefin adhesive film 100' of the second embodiment of the present invention does not require the adhesive layer 1 formed on the support layer 2 by co-extrusion to be directly thermally laminated with the metal aluminum foil AF and bonded with another polyester adhesive or polyurethane adhesive.

[0071] [Advantageous Effects of the Embodiments] As an advantageous effect of the present invention, the polyolefin adhesive film of the present invention has the following technical features: "a support layer which is a polypropylene film", "an adhesive layer formed on one side of the support layer by coextrusion", and "the adhesive layer is a first polyolefin copolymer modified with maleic anhydride. The first polyolefin copolymer is formed by copolymerizing at least two types of C2-C4 olefin molecules. The first graft ratio of the maleic anhydride in the first polyolefin copolymer is 0.5%-5%, and the first melt index of the first polyolefin copolymer is 3g / 10min-5g / 10min". Therefore, the adhesive layer formed on the support layer by coextrusion can be directly thermally laminated to the metal aluminum foil, eliminating the need to use another polyester adhesive or polyurethane adhesive to bond it.

[0072] The polyolefin adhesive film according to the present invention has self-adhesiveness and can solve the problem of volatile organic solvent (VOC) volatilization in the conventional technology. In addition, the polyolefin adhesive film according to the embodiment of the present invention can solve the problem of strength reduction caused by a hot and humid environment for a long time in the conventional dry composite polyolefin film / aluminum foil packaging material.

[0073] The above disclosure is merely a preferred embodiment of the present invention, and the scope of the claims of the present invention is not limited thereto. Therefore, all equivalent technical modifications made by utilizing the contents of the specification and drawings of the present invention are included in the scope of the claims of the present invention. [Explanation of symbols]

[0074] <Examples of the present invention> 100,100'...Polyolefin adhesive film 1...Adhesive layer 2…Support layer 3…Heat seal layer T1…First thickness T2: Second thickness T3…Third thickness AF…Metallic aluminum foil <Prior Art> AF…Metallic aluminum foil GL…Adhesive layer PL…Polymer membrane

Claims

1. a support layer which is a cast polypropylene film; and an adhesive layer formed on one side of the support layer by coextrusion, The support layer includes a propylene block polymer, a vinyl elastomer, and a second polyolefin copolymer, the adhesive layer comprises a first polyolefin copolymer modified with maleic anhydride; In the adhesive layer, the content of the first polyolefin copolymer is 90 wt % or more, The first polyolefin copolymer is formed by copolymerizing at least two of C2 to C4 olefin molecules, and a first graft ratio of the maleic anhydride in the first polyolefin copolymer is 0.5% to 5%, and a first melt index of the first polyolefin copolymer is 3 g / 10 min to 5 g / 10 min.

2. 2. The polyolefin adhesive film of claim 1, wherein in the adhesive layer, the first melt index of the first polyolefin copolymer is 3 g / 10 min to 4 g / 10 min.

3. 2. The polyolefin adhesive film of claim 1, wherein in the support layer, the propylene block polymer comprises a block composed of an ethylene propylene elastic rubber, the weight percent of the ethylene propylene elastic rubber in the propylene block polymer is 18% or more, and the vinyl-based elastomer is an ethylene / butene elastomer and the weight percent of ethylene in the vinyl-based elastomer is 30% or more.

4. The second polyolefin copolymer in the support layer is modified with maleic anhydride and formed by copolymerization of at least two of C2-C4 olefin molecules, the second grafting rate of the maleic anhydride in the second polyolefin copolymer is 0.5%-5%, and the second melt index of the second polyolefin copolymer is 3g / 10min-5g / 10min. The polyolefin adhesive film of claim 1.

5. 5. The polyolefin adhesive film according to claim 4, wherein in the support layer, the content of the propylene block polymer is 50 wt % to 90 wt %, the content of the vinyl elastomer is 5 wt % to 30 wt %, and the content of the second polyolefin copolymer modified with maleic anhydride is 5 wt % to 20 wt %, with the total weight of the support layer being 100 wt %.

6. 10. The polyolefin adhesive film of claim 1, further comprising a heat seal layer formed on the other side of the support layer by coextrusion.

7. 7. The polyolefin adhesive film of claim 6, wherein the heat seal layer is a propylene polymer, the propylene polymer being at least one of a propylene copolymer (co-PP) and a propylene homopolymer (homo-PP).

8. The polyolefin adhesive film according to claim 6, wherein the heat seal strength of the heat seal layer of the polyolefin adhesive film, measured according to QB / T2358-1998, is 80 N / 15 mm or more.

9. 7. The polyolefin adhesive film of claim 6, wherein the adhesive layer has a first thickness of 4 μm to 12 μm, the support layer has a second thickness of 15 μm to 35 μm, and the heat seal layer has a third thickness of 4 μm to 12 μm.

10. The polyolefin adhesive film according to any one of claims 1 to 9, wherein the polyolefin adhesive film is bonded to a metal aluminum foil via the adhesive layer, so that the peel strength between the polyolefin adhesive film and the metal aluminum foil is 10 N / 15 mm or more.

11. The polyolefin adhesive film according to claim 10, wherein the aluminum-plastic laminate film formed by bonding the polyolefin adhesive film and the metal aluminum foil has a peel strength of more than 8.5 N / 15 mm after immersion in an electrolyte environment at 85°C for 168 hours.

Citation Information

Patent Citations

  • Production of laminated body

    JP1989027923A

  • Package excellent in content resistance and production thereof

    JP1997164639A

  • Adhesive resin composition and laminated product

    JP2002088328A

  • Multilayered polyester oriented bottle with improved moisture resistance and transparency

    JP2004182304A

  • Binder for multilayer structure

    JP2017509723A